1988
DOI: 10.1084/jem.168.2.589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fetal and adult functional B cell repertoires by analysis of VH gene family expression.

Abstract: The functional B cell repertoire in BALB/c mice was assessed at various stages in ontogeny. This was done by analyzing VH gene family expression using the sensitive technique of in situ hybridization. The B cell repertoire was probed with the mitogen, LPS, and the antigen DNP. DNP was chosen because B cells responsive to this hapten appear very early in ontogeny. The APCs that developed after stimulation with LPS or DNP were analyzed for VH gene expression by in situ hybridization of individual cells using rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
41
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 51 publications
(69 reference statements)
7
41
3
Order By: Relevance
“…Failure to express an extensive and suitable BCR repertoire by B cells could be a potential reason for the lack of Ag-specific Ab response not only in IL-7 2/2 mice but also in young wild-type mice. The B cell repertoire in adult wild-type mice represents all VH genes, even more so those, that are distal to the DJ segments (43)(44)(45). In contrast, B cells of young wild-type mice preferentially express VH genes proximal to DJ but not the major families of VH genes that are distal to DJ and known to be critical for extensive BCR diversity (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to express an extensive and suitable BCR repertoire by B cells could be a potential reason for the lack of Ag-specific Ab response not only in IL-7 2/2 mice but also in young wild-type mice. The B cell repertoire in adult wild-type mice represents all VH genes, even more so those, that are distal to the DJ segments (43)(44)(45). In contrast, B cells of young wild-type mice preferentially express VH genes proximal to DJ but not the major families of VH genes that are distal to DJ and known to be critical for extensive BCR diversity (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The B cell repertoire in adult wild-type mice represents all VH genes, even more so those, that are distal to the DJ segments (43)(44)(45). In contrast, B cells of young wild-type mice preferentially express VH genes proximal to DJ but not the major families of VH genes that are distal to DJ and known to be critical for extensive BCR diversity (43)(44)(45). Similarly, in the absence of IL-7-mediated signaling, the usage of several large families of VH genes distal to DJ in the IgH locus does not occur because of a constraint in the accessibility of distal VH genes for VDJ recombination events (41,62).…”
Section: Discussionmentioning
confidence: 99%
“…Is there a single homogeneous developmental lineage throughout this period or is the FT developmental lineage itself comprised of distinct developmental sublineages? It is known that fetal liver-derived B cells have V gene repertoires skewed towards the D-proximal families (36) and with few N region additions. Using I-A expression as a FT lineage marker, similar analyses of V gene usage and N region additions for FT B cells generated in the spleens, livers, and PerC would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…4 Most natural TCR and Ig RSS vary from the consensus RSS, and this variation could result in differences in rearrangement frequency (17). In these cases, the chromosomal location would be irrelevant, and thus could explain the inconsistent correlation of high frequency of rearrangement with proximal chromosomal location for only some, but not other, V and J loci.…”
mentioning
confidence: 99%
“…An example of unusually high frequency of rearrangement is observed with the 81X gene, which is the most 3Ј functional V H gene in the murine V H locus. Many laboratories have observed that this V H gene family rearranges very frequently early in ontogeny and also in the adult bone marrow (1)(2)(3)(4)(5)(6)(7)(8)(9). The overuse of the 7183 family, especially 81X, gave rise to the chromosomal proximity hypothesis of Alt and colleagues, which proposed that the rearrangement mechanism preferentially rearranges genes that are in closer proximity in the chromosome (1,10).…”
mentioning
confidence: 99%